Peran Literasi Kesehatan dalam Meningkatkan Kepatuhan Masyarakat terhadap Program Pencegahan Penyakit - Nurfitriah, Amelia (Maliki Interdisciplinary Journal, 2026)
Health literacy is a crucial determinant in shaping preventive health behavior and public compliance with disease prevention programs. Low levels of health literacy contribute to poor adherence to clean and healthy lifestyle behaviors, medication adherence, and participation in public health programs. This article aims to analyze the role of health literacy in improving community compliance with disease prevention programs based on empirical evidence from previous studies. The method used is a literature review of relevant national journals. The findings indicate that higher health literacy is significantly associated with better compliance in preventing both communicable and non-communicable diseases. Health literacy influences individuals’ ability to access, understand, and apply health information, thereby affecting appropriate health decision-making. Therefore, strengthening health literacy should be a key strategy in planning promotive and preventive health programs.